Reconfigurasi Manajemen Produksi dan Operasi di Era Industri 4.0: Tinjauan Literatur Sistematis - Yudhi Yanuar Fiqri (Universitas Nusantara PGRI Kediri, 2026)
This study aims to systematically synthesize the literature on production and operations management reconfiguration in the Industry 4.0 era and develop a conceptual framework that integrates technological, organizational, and human dimensions. The method used is a systematic literature review with the PRISMA protocol through searching articles in the Scopus and Web of Science databases. The search strategy used keywords related to reconfiguration, production and operations management, and Industry 4.0, resulting in an initial 200 publications. After going through the process of eliminating duplicates, screening titles and abstracts, abstract assessment, and full-text screening based on strict inclusion and exclusion criteria, 40 articles were obtained for further analysis. Thematic analysis was used to identify patterns, themes, and research gaps. The results show four main themes: production planning and control architecture, manufacturing system reconfiguration management, operational resilience and risk management, and complexity management and technology integration. This study produces a three-dimensional conceptual framework that integrates technology, organization, and people as the foundation for successful production and operations management reconfiguration. These findings contribute to the development of science by providing a comprehensive synthesis and shifting the paradigm towards a human-centric Industry 5.0.